Desain Reaktor Alkilasi Pada Praprancangan Pabrik Linier Alkil Benzen (LAB) Dari Benzen Dengan Proses UOP/CEPSA (Detal Process) - Khobar Bahari Pane; Ida Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Linear alkyl benzene (C6H5CnH2n+1) is one of the organic compound used as a raw material in the detergent industry because it has a high degradation rate and it is biodegradable. The increasing use of detergents, the linear alkyl benzene industry will also be growing. This plant is designed to produce 80,000 tons per year of linear alkyl benzene (LAB). One of the main equipment in this plant is the alkylation reactor. This equipment is designed to react mono olefins and benzene to produce linear alkyl benzene (LAB) and heavy alkyl benzene (HAB) as side products with ZSM-5 catalyst via alkylation reaction. This reactor type is a fixed bed multitube reactor with cooling water as an internal cooler in the shell and this reactor is operated isothermally at temperature input and output of 403 K and pressure of 2.73 bar. The feed flow rate is 44680,877 kg per hour consisting of benzene and a mixmonoolefin. The height of this reactor is 8.85 m and a diameter of 3.45 m with torispherical flanged and dished head and skirt support. Keywords: Alkylation, Linear Alkyl Benzene, Reactor Fixed Bed Multitube, ZSM-5 catalyst